Fabrication of self-organized epitaxial fcc-Ag(110)-oriented nanorods by a Ti seed-layer-assisted thermal agglomeration method. (17th February 2015) - Kamiko, Masao; Suenaga, Ryo; Koo, Jung-Woo; Nose, Kenji; Kyuno, Kentaro; Ha, Jae-Geun
Abstract: We analyzed the effect of a Ti seed layer on the agglomeration of Ag films grown on MgO(110) substrates. The samples were deposited at room temperature and post-annealed at 350 °C for 4 h. Atomic force microscopy observations indicated that the insertion of the Ti seed layer between the substrate and Ag promoted the agglomeration, leading to nanorod formation. X-ray diffraction analyses showed that the Ag/Ti film grown on MgO(110) substrate yielded fcc-Ag(110)-oriented epitaxial nanorods. Additionally, typical optical absorbance spectra of the Ag nanorods were obtained in the Ag/Ti films.